Everolimus for patients with mantle cell lymphoma refractory to or intolerant of bortezomib: multicentre, single‐arm, phase 2 study. (2nd March 2014) - Wang, Michael; Popplewell, Leslie L.; Collins, Robert H.; Winter, Jane N.; Goy, Andre; Kaminski, Mark S.; Bartlett, Nancy L.; Johnston, Patrick B.; Lister, John; Fanning, Suzanne R.; Tuscano, Joseph M.; Beck, J. Thaddeus; et al.
Summary The multicentre, open‐label, two‐stage, single‐arm, phase 2, PILLAR (PIvotaL Lymphoma triAls of RAD001)‐1 study (NCT00702052) assessed the efficacy and safety of everolimus 10 mg/d in adults with confirmed mantle cell lymphoma (MCL) refractory to or intolerant of bortezomib who received ≥1 other antineoplastic agent, either separately or in combination with bortezomib. Primary endpoint was overall response rate (ORR) per investigator review according to the response criteria for malignant lymphoma. Secondary endpoints included progression‐free survival (PFS), overall survival (OS) and safety. Fifty‐eight patients were enrolled from August 2008–January 2011. Five partial responses were observed (ORR 8·6%; 90% confidence interval [CI] 3·5–17·3%); the study did not meet the prespecified objective of ≥8 objective responses among 57 patients. Median PFS and OS were 4·4 months (95% CI 3·5–6·1) and 16·9 months (95% CI 14·4–29·9), respectively. Grade 3/4 non‐haematological toxicities occurred in 70·7% of patients. Based on laboratory values, grade 3/4 thrombocytopenia, neutropenia and anaemia occurred in 13·8%, 13·8% and 8·6% of patients, respectively. Everolimus demonstrated modest activity and acceptable tolerability in heavily pretreated patients with MCL refractory to or intolerant of bortezomib. Future studies evaluating everolimus in a less refractory population or in combination with other targeted therapies in refractory MCL are warranted.